Avaliação do desenvolvimento da Salicorni neei Lag Submetida a diferentes espaçamentos de cultivo. - Figueiredo, Caio Franklin Vieira de (2020)
In Brazil, saline soils occupy about 160,000 km2 or 2% of the national territory, with a predominance in the Northeast semi-arid region. In northeastern Brazil, the use of water resources is limited due to the high concentration of salts, since much of the region is located on crystal line rocks and contact, for a long time, underground, between water and this type of rock, leads to a salinization process. The most used method for water desalination in the Northeast has been the process of reverse osmosis that also implies the generation of a wastewater (tailings). The cultivation of halophytes in areas degraded by salinization is an alternative for soil reuse and destination for effluents with high salinity. Among the halophytes belonging to the Brazilian flora, salicornia is a plant that tolerates high levels of interstitial salinity and which can act in the phytoremediation of areas subject to degradation by salts. Thus, in this study, we analyzed the effect of spacing between lines and between plants on the growth and productivity of the halophyte Salicornia neei irrigated with desalinator tailings. The cultivation was carried out in beds whose spacings corresponded to 5, 10, 15, 20, 30 e 40 cm between lines and plants, for six months. After collection, laboratory and statistical analyses, the results indicate that most bromatological determinations presented more efficient values in spacing 15x15cm: dry matter weight - PMS (9,353.0 kg/ha); total nitrogen - NT (3.09%); total protein - PT (19.31 %); acid detergent fiber - FDA (30.50 %); neutral detergent fiber - NDF (38.15 %); total fiber - FT (26.71 %) and Ethereal Extract - EE (1.91 %). Regarding phytoextraction by Salicornia neei, the most efficient spacings were 20x20cm for sodium - Na (15.5 %); 30x30 cm for potassium - K (3.00 %) and 40x40 cm for calcium - Ca (4.18%) and magnesium - Mg (3.90%).